Wild birds as a probable source of colonization of campylobacter in poultry - M. Y., Elnohi; Abdul Aziz, Saleha; Abu, Jalila; Bejo, Siti Khairani; Puan, Chong Leong; M. I., Jalo; N., Fauziah (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The study was carried out to detect the presence of Campylobacter in wild birds caught around chicken and duck farms and also in the chickens and ducks in the farms. Of the 70 birds belonging to six species, 18.6% were positive for Campylobacter and of the 101 chickens and 104 ducks sampled, 40% were Campylobacter-positive. Campylobacter jejuni were frequently isolated from birds, chickens and ducks. The wild birds may play a role in the spread of campylobacters to chickens in the farms.